Research on the multiple subarray-pairs interferometric algorithm used in high resolution multibeam bathymetric system - ZHOU Tian1; LI Shan1; LI Hai-sen1; LIU Xiao1 (Tongxin xuebao)
An optimized subarray configuration was analyzed theoretically for the performance enhancement of inter-ferometric algorithm used in multibeam bathymetric system,and the relationship between phase ambiguity existed in in-terferometric algorithm and subarray configuration was deduced theoretically.On the basis,a new multiple subarray-pairs interferometric algorithm was proposed,which not only solved the difficulties of phase ambiguity unwrapping highly ef-ficient,but improved the resolution and coverage performance of bathymetric estimation of system.The processing re-sults of experiment data prove the efficiency,practicality and superiority of the new algorithm.